DIDACTIC TERMS AND CONDITIONS OF USING COMPUTER DESIGN TOOLS IN THE TRAINING OF SPECIALISTS IN THE FIELD OF TRANSPORTATION ENGINEERING - Kulmuradov Dilshod Istamovich (Journals Park Publishing, 2022)
In this article, you will get acquainted with the conditions for using computerized design tools in the training of specialists in the field of vehicle engineering. In addition, suggestions were given to give students knowledge on computer design.
Keywords: Science,; electronic virtual library,; SDAS